The Effect of Inflation, Exchange Rate and Interest Rate on Indonesian Nutmeg Exports to China Market - Tessa Oktaviani Dahlan; Nuriah Yuliati; Taufik Setyadi (Ekonomis: Journal of Economics and Business, 2026)
The objective of this study is to examine the trend of Indonesian nutmeg exports to the global market, with a particular focus on the Chinese market, and to assess the impact of macroeconomic variables, including inflation, exchange rates, and interest rates, on nutmeg exports. The data set spans the period from 1990 to 2023. The forecasting of export volume employs the ARIMA model, while the measurement of the impact of macroeconomic factors utilizes multiple linear regression. Regression analysis reveals that the inflation variable exerts no statistically significant effect on long-term export trends (p-value 0.7897 > 0.05). The exchange rate variable has a significant positive effect on nutmeg exports in the long term (p-value 0.0000 < 0.05), indicating that a depreciation of the rupiah increases nutmeg exports in the international market. The results indicate that interest rates have a significant negative effect on exports in the long term (p-value 0.0146 < 0.05). This is due to the fact that an increase in interest rates leads to an increase in production and borrowing costs, which in turn reduces export volumes. Furthermore, in the short term, none of the macroeconomic variables demonstrated a significant impact. The findings of this study indicate that the limited influence of macroeconomic factors in the short term can be attributed to the distinctive characteristics of nutmeg as a niche market commodity and the prevalence of cooperative agreements between firms. Nutmeg has essential uses and unique qualities that render its demand relatively stable and insensitive to price fluctuations or macroeconomic changes. This indicates that nutmeg, with its segmented is capable of maintaining consistent export volumes despite short-term fluctuations in economic conditions. In order to enhance competitiveness on the global market, a more focused marketing strategy and market diversification that incorporates the distinctive attributes of this commodity are essential.